(untitled) - Sadker, Myra Pollack (Boston, 2005)
The most reader friendly text in its field, the seventh edition presents a comprehensive overview of education in America. It provides in-depth commentary on educational history, philosophy, and governance, while giving special attention to current critical topics such as student diversity, standards and testing
Keywords: Teaching,Lịch sử giáo dục Hoa Kỳ,Education; History; United States